Impact of Open-Angle Glaucoma Severity on Vision-Related Quality of Life: A Cross-Sectional Study in a Single Center in Indonesia - Rino Agustian Praja; Andrini Ariesti; Hendriati; Muhammad Hidayat; Irayanti; Julita (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Glaucoma is a progressive optic neuropathy characterized by the gradual loss of retinal ganglion cells (RGCs) and their axons, leading to irreversible visual field loss. This study aimed to investigate the relationship between the severity of primary open-angle glaucoma (POAG) and vision-related quality of life (VRQoL) in a single center in Indonesia. Methods: A cross-sectional study was conducted at the eye polyclinic of Dr. M. Djamil General Hospital, Padang, Indonesia, from June to August 2024. A total of 54 patients with POAG were included and categorized into mild, moderate, and severe groups based on their cup-to-disc ratio and visual field index (VFI). VRQoL was assessed using the Indonesian version of the National Eye Institute Visual Function Questionnaire (NEI-VFQ 25). Results: The mean VRQoL score was significantly lower in the severe group (60.63 ± 13.04) compared to the moderate (81.79 ± 10.42) and mild (85.04 ± 10.52) groups (p = 0.000). A strong negative correlation was observed between glaucoma severity and VRQoL (r = -0.667, p = 0.000). The social functioning subscale showed the strongest correlation with severity (r = -0.573, p = 0.000). Conclusion: The severity of POAG significantly impacts VRQoL, with more severe disease associated with lower QoL scores. The social functioning domain appears to be particularly affected. These findings underscore the importance of comprehensive glaucoma management that addresses not only clinical parameters but also the patient's overall quality of life.